"A Postgame Interview for the Ages": Richard Sherman and the Dialectical Rhetoric of Racial Neoliberalism. (August 2016) - Tompkins, Joe
This essay analyzes articulations of race and power as they surfaced in the media uproar surrounding National Football League (NFL) star Richard Sherman's notorious 2014 National Football Conference (NFC) Championship post-game "interview for the ages." It charts two dialectical poles of representation: overtly racist denunciations of Sherman as a classless "thug" and counter-representations of self-enterprising talent. I argue these competing images register "permissible narratives of difference" that underwrite a neoliberal, post-racial project. The article thus explores how Sherman's newfound celebrity authorizes "official antiracisms" of post-racial rhetoric, which foreclose alternatives to the privatization and depoliticization of racial discourse.